TRAINING STRATEGIES FOR THE INITIATION OF LEARNING THE ARCHITECTURAL PROJECT - Alba-Dorado, María Isabel; González Bandera, María Isabel (IATED Academy, 2020)
The first courses of the Architectural Projects subject have an initiatory character. This learning represents the student's first contact with the knowledge and the architectural creation. This leads in some cases to a new discovery and a break with the concept of architecture that the student had before starting the degree. This learning has all the symbology involved in embarking on a path full of uncertainties and difficulties that can only be overcome with a continued effort. The objective of this communication is to define a series of didactic strategies for the first years of architecture student training. These are intended to make the student develop attitudes and skills that encourage creative thinking. Likewise, it will be objective of these strategies to promote the capacity for criticism, analysis and reflection. For this, we start from a teaching model in which training prevails over information. It is proposed to generate more flexible learning situations and itineraries that facilitate and support subsequent continuous training. Furthermore, a more critical and profound intellectual development is contemplated, which enables the student to generate knowledge, but also to acquire autonomy of thought. As a work methodology, it is proposed to define a series of training strategies. These will be oriented to show an attitude towards the project and to encourage, stimulate and involve students in their learning process. These aim to help students develop their ability to learn to learn. The result will be the definition of a series of specific training strategies for these first years of training. These will aim to familiarize the student with the concepts and methods of the architectural project process. These strategies seek to support a teaching that contemplates the complexity of the architectural fact and promotes deep and significant learning processes.
Keywords: Arquitectura - Estudio y enseñanza; Proyectos de arquitectura; training strategies; teaching; learning; architectural project